Nutrient consumption and dietary patterns in Malawi - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This poster uses data from the fourth Integrated Household Survey (IHS4) conducted in all 28 districts and the four major cities of Malawi in 2016/17. The IHS is a nationally representative survey which collects multitopic household and community data, including on the consumption of approximately 150 food items. The data was collected from 12,447 households over one calendar year to account for seasonality. The IHS4 consumption estimates were combined with data on the nutrient content of foods from the Food and Agriculture Organization to estimate nutrient consumption per person per day.